Uric Acid Sensor Based on PEDOT:PSS Modified Screen-Printed Carbon Electrode Fabricated with a Simple Painting Technique - Wulan Tri Wahyuni; Rudi Heryanto; Eti Rohaeti; Achmad Fauzi; Budi Riza Putra (Jurnal Kimia Sains dan Aplikasi, 2021)
A screen-printed carbon electrode is a suitable electrode for electrochemical sensors due to its simplicity and portability. This study aimed to fabricate a screen-printed carbon electrode modified with poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (SPCE-PEDOT:PSS) to improve the electrochemical performance for uric acid detection. The SPCE was fabricated using a layer-by-layer painting process of conductive ink consisting of graphite as a conductive material, polystyrene as a polymeric binder, and dichloromethane solvent on a polyvinyl chloride paper substrate. The fabricated SPCE was then modified with PEDOT:PSS by a drop-casting method. The characterization of SPCE-PEDOT:PSS surface morphology was performed using the scanning electron microscopy technique. The SPCE-PEDOT:PSS provided an acceptable linearity (R2 = 0.9985, 0.9993, 0.9985), sensitivity (0.070, 0.015, 0.024 µA/µM), precision (%RSD = 2.70%, 2.89%, 2.40%), limit of detection (1.61 µM, 1.14 µM, 1.62 µM), and limit of quantitation (5.37 µM, 3.81 µM to 5.39 µM) in measurement of uric acid standard solution using cyclic voltammetry, amperometry, and differential pulse voltammetry techniques, respectively. The studies using SPCE-PEDOT:PSS indicated that the electrode could be applied in the electrochemical measurement of uric acid in the human urine sample.